2018
DOI: 10.2147/ppa.s159620
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences in Italy: health state utilities associated with attributes of weekly injection devices for treatment of type 2 diabetes

Abstract: ObjectivesSeveral glucagon-like peptide-1 receptor agonists are administered as weekly injections for treatment of type 2 diabetes (T2D). These medications vary in their injection processes, and a recent study in the UK found that these differences had an impact on patient preference and health state utilities. The purpose of this study was to replicate the UK study in Italy to examine preferences of an Italian patient sample, while allowing for comparison between utilities in the UK and Italy.Materials and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
0
4
0
Order By: Relevance
“… 9 Two further studies conducted in people with T2D in the UK and Italy (both with identical methodology) used TTO methods to determine the QoL impact of process characteristics of a weekly injection including requirement for reconstitution, needle handling and waiting. 19 , 20 In the UK-based study, a weekly injection with no inconvenience was associated with a disutility of −0.010 relative to oral treatment alone. In contrast, a weekly injection that required reconstitution, needle handling and waiting time was associated with a disutility of −0.030 relative to oral treatment alone and −0.020 relative to a weekly injection with no inconvenience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Two further studies conducted in people with T2D in the UK and Italy (both with identical methodology) used TTO methods to determine the QoL impact of process characteristics of a weekly injection including requirement for reconstitution, needle handling and waiting. 19 , 20 In the UK-based study, a weekly injection with no inconvenience was associated with a disutility of −0.010 relative to oral treatment alone. In contrast, a weekly injection that required reconstitution, needle handling and waiting time was associated with a disutility of −0.030 relative to oral treatment alone and −0.020 relative to a weekly injection with no inconvenience.…”
Section: Resultsmentioning
confidence: 99%
“… 19 Similar findings were reported in the Italian study where the disutility for a weekly injection with no inconvenience relative to oral treatment alone was −0.009 and the disutility for a weekly injection with reconstitution, needle handling and waiting was −0.032 relative to oral treatment alone and −0.022 relative to a weekly injection with no inconveniences. 20 Another further study by the same authors compared process characteristics associated with a concentrated formulation of insulin versus standard insulin with attributes of the concentrated formulation including less injection volume, less effort to press the injection button and fewer pens required. Matza et al used TTO methodology to determine mean utility (SD) values of 0.889 (0.103) with the concentrated insulin formulation versus 0.882 (0.104) with the standard insulin formulation.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 162 records were retrieved in the search and screened using the title and abstract. (figure 1) From these, 86 full-text articles were assessed for eligibility and 17 studies comprising 7296 patients were included in this review [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (table 1). We did not identify studies reported values and preferences of SGLT-2i and all eligible studies evaluated GLP-1 RA.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…[19][20][21][22][23] Furthermore, 12 studies comprising a total of 4634 patients evaluated preferences between, at least, two different GLP-1 RA medications or related injection devices, taking into account clinical attributes and/or device-related ones such as dosing, application frequency or characteristics of the application device. [24][25][26][27][28][29][30][31][32][33][34][35] Mean age of participants in the included studies ranged between 52.7 and 63.9 years. Most studies reporting duration of diabetes and included patients at least 1 year after diagnosis.…”
Section: Study Characteristicsmentioning
confidence: 99%